The new military junta (f.l.t.r.): Coutinho, Neto, Costa Gomes, De Spinola, Silverio Marques and Galvao de Melo
The new military junta (f.l.t.r.): Coutinho, Neto, Costa Gomes, De Spinola, Silverio Marques and Galvao de Melo.